The Influence Of Green Marketing Mix On The Decision To Purchase Cosmetic Products The Body Shop In Jakarta - Lucky Dhananjaya; Muchsin Saggaf Shihab (Sean Institute, 2024)
Consumer purchasing decisions are important for companies. For this reason, it is important to carry out an analysis of the factors that influence consumer purchasing decisions on The Body Shop products. The aim of this research is to analyze the influence of the green marketing mix consisting of environmentally friendly products, prices, environmentally friendly distribution channels and environmentally friendly promotions on purchasing decisions. The research method used was a quantitative method with sampling using simple random sampling with a sample of 250 respondents, then the data was analyzed using SEM-PLS analysis. Based on the results and discussion, it can be concluded: (1) The Influence of Green Products on Purchasing Decisions. There is a significant positive influence between green products on purchasing decisions. (2) The Effect of Green Prices on Purchasing Decisions. There is a significant positive influence between green prices on purchasing decisions. (3) The Influence of Green Place on Purchasing Decisions. There is a significant positive influence between green place on purchasing decisions. (4) The Effect of Green Promotion on Purchasing Decisions. There is a significant positive influence between green promotion on purchasing decisions.